Metal‐Free Route to Precise Synthesis of Poly(propylene oxide) and Its Blocks with High Activity - Zhang, Cheng‐Jian; Duan, Han‐Yi; Hu, Lan‐Fang; Zhang, Cheng‐Hui; Zhang, Xing‐Hong (ChemSusChem, 2018)
The fast and living ring‐opening polymerization (ROP) of propylene oxide (PO) by metal‐free catalysis is reported. By using triethyl borane (TEB) and organic Lewis bases (LBs, e.g.: phosphazene base, amidine and guanidine) as the catalysts, various alkyl alcohols can effectively initiate the ROP of PO, yielding tailor‐made poly(propylene oxide)s (PPOs) with high regioregularity, predictable molecular weights, and narrow dispersity approaching Poisson distribution. The TEB/LB catalysts present unprecedentedly high activity (turnover frequency of up to 7500 h−1) and a truly living character for the polymerization, as evidenced by kinetic studies that showed fast initiation and growth, unobserved chain‐transfer to PO, chain extension reactions, and the synthesis of various PPO‐based block copolymers with narrow dispersities (Đ<1.1). Poisson project: The metal‐free, fast, and living ring‐opening polymerization of propylene oxide is performed by a unique masking anion strategy, yielding tailor‐made poly(propylene oxide)s with unprecedented activity, high regioregularity, predictable molecular weights, and narrow dispersity approaching Poisson distribution.